2011
DOI: 10.1089/cell.2010.0075
|View full text |Cite
|
Sign up to set email alerts
|

SAF-A Has a Role in Transcriptional Regulation ofOct4in ES Cells Through Promoter Binding

Abstract: Methodologies to reprogram somatic cells into patient-specific pluripotent cells, which could potentially be used in personalized drug discovery and cell replacement therapies, are currently under development. Oct4 activation is essential for successful reprogramming and pluripotency of embryonic stem (ES) cells, albeit molecular details of Oct4 activation are not completely understood. Here we report that endogenous SAF-A is involved in regulation of Oct4 expression, binds the Oct4 proximal promoter in ES cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 46 publications
(58 reference statements)
0
31
0
Order By: Relevance
“…To overcome the variable percentage of XO cells in the starting populations, each experiment was normalised to the matched Nons control ( Figure 5D). Unexpectedly, knockdown of Hnrnpu caused a rapid loss of double positivity prior to weaning into differentiation media, likely due to the requirement of Hnrnpu for pluripotency (Vizlin-Hodzic et al, 2011) and suggesting Xmas ESCs may be useful for the identification of novel pluripotency factors. To circumvent the role of Hnrnpu in pluripotency and instead test its function in XCI, we transduced cells with shRNA at day 2 of differentiation, so that knockdown takes effect following exit from pluripotency.…”
Section: Xmas Escs Have the Capacity To Detect Impaired XCImentioning
confidence: 99%
“…To overcome the variable percentage of XO cells in the starting populations, each experiment was normalised to the matched Nons control ( Figure 5D). Unexpectedly, knockdown of Hnrnpu caused a rapid loss of double positivity prior to weaning into differentiation media, likely due to the requirement of Hnrnpu for pluripotency (Vizlin-Hodzic et al, 2011) and suggesting Xmas ESCs may be useful for the identification of novel pluripotency factors. To circumvent the role of Hnrnpu in pluripotency and instead test its function in XCI, we transduced cells with shRNA at day 2 of differentiation, so that knockdown takes effect following exit from pluripotency.…”
Section: Xmas Escs Have the Capacity To Detect Impaired XCImentioning
confidence: 99%
“…hnRNP U like-1 protein (hnRNPUL1) is considered as a novel surface molecule marker on undifferentiated human ES cells [60]. In addition, hnRNP U maintains ES cell pluripotency as a modulator of pluripotency factor OCT4 through direct binding to OCT4 proximal promoter and activation of OCT4 gene expression [68]. …”
Section: Hnrnps In Maintenance Of Stem Cell Self-renewal and Develmentioning
confidence: 99%
“…SAF-A was found on the Oct4 promoter only when the gene is actively transcribed in murine ESCs, depending on LIF, and gene silencing of SAF-A in ESCs resulted in down regulation of Oct4 (Vizlin-Hodzic et al, 2011). Other Oct4 modulators have been reported that in similarity with SAF-A are in complex with RNA polymerase II (Ding et al, 2009;Ponnusamy et al, 2009).…”
Section: Molecular Mechanisms Of Reprogrammingmentioning
confidence: 99%